2018
DOI: 10.1038/nm.4483
|View full text |Cite
|
Sign up to set email alerts
|

A histone deacetylase 3–dependent pathway delimits peripheral myelin growth and functional regeneration

Abstract: Deficits in Schwann cell–mediated remyelination impair functional restoration after nerve damage, contributing to peripheral neuropathies. The mechanisms mediating block of remyelination remain elusive. Here, through small-molecule screening focusing on epigenetic modulators, we identified histone deacetylase 3 (HDAC3; a histone-modifying enzyme) as a potent inhibitor of peripheral myelinogenesis. Inhibition of HDAC3 enhanced myelin growth and regeneration and improved functional recovery after peripheral nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 60 publications
2
84
3
Order By: Relevance
“…It has become clear that epigenomic changes are important for such reprogramming events, employing mechanisms of gene activation and derepression (Brügger et al 2017; He et al 2018; Hung et al 2015; Jacob 2017; Ma and Svaren 2018). Our previous studies identified the association of trimethylation at Lys27 of histone H3 tail (H3K27me3) at promoters of many genes that become activated after peripheral nerve injury, and we found that the demethylation is required for full activation of some repair genes (Ma et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has become clear that epigenomic changes are important for such reprogramming events, employing mechanisms of gene activation and derepression (Brügger et al 2017; He et al 2018; Hung et al 2015; Jacob 2017; Ma and Svaren 2018). Our previous studies identified the association of trimethylation at Lys27 of histone H3 tail (H3K27me3) at promoters of many genes that become activated after peripheral nerve injury, and we found that the demethylation is required for full activation of some repair genes (Ma et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent article on the effect of TSA on peripheral neurodegeneration, Kim et al (32) reported that TSA successfully inhibited the phenotypes of peripheral neurodegeneration including myelin fragmentation, axonal degradation, and transdedifferentiation and proliferation of Schwann cells. In addition, He et al (33) found that the inhibition of HDAC3 with RGFP966 or PDA106 increased myelin growth and regeneration after peripheral nerve damage in mice. In line with this, Schwann cell-specific deletion of Hdac3 in mice also enhanced myelin thickness in sciatic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent research, three inhibitors that preferentially target HDAC3, pimelic diphenylamide compound 106 (PDA106), RGFP966, and apicidin, were found to markedly elevate the expression of early growth response 2 (EGR2) in developing SCs, which is a key promyelinating regulator and serves an indicator of myelinogenic potential. Besides, treatment with HDAC3 inhibitors resulted in an expansion of cellular processes, actin cytoskeleton augmentation and induction of myelin protein expression in vitro (He et al., ). Sustained ablation of Hdac3 in developing immature or pre‐myelinating SCs mimics the effect of HDAC3 inhibitors and results in myelin sheath overgrowth and hypermyelination in the mice.…”
Section: Hdacs In Peripheral Nervous System Myelinationmentioning
confidence: 99%
“…In a recent study, HDAC3 was revealed to pair with P300 histone acetyltransferase in differentiating SCs and target a set of genes that coincide with enhancer elements marked by H3K27ac (histone H3 lysine27 acetylation; He et al., ). This observation posits HDAC3/P300 coordination at the apex of a gene regulatory network that controls both activation and inhibition of SCs myelination via distinct mechanisms.…”
Section: Hdacs In Peripheral Nervous System Myelinationmentioning
confidence: 99%
See 1 more Smart Citation